Bilateral Pulmonary Thromboembolism After Moderna Vaccination in a Healthy Candidate - Mamun, SMAA; Sharkar, S; Shaheed, Saika (Bangladesh Journal of Medicine, 2022)
Vaccination against severe acute respiratory syndrome corona virus 2 (SARS-CoV-2), the causative agent of corona virus Disease 2019 (COVID-19) is a critical strategy to overcome the COVID-19 pandemic. Multiple SARS-CoV-2 vaccines have been developed in a rapid timeframe to combat the pandemic. As with any other medication, there have been adverse effects associated with the use of vaccines ranging from mild symptoms to life threatening side effects that have led to mortality. One of the more serious adverse effects associated with a number of vaccines such as those produced by AstraZeneca/Oxford and Pfizer BioN-tech is a phenomenon known as vaccine-induced immune thrombotic thrombocytopenia leading to thrombosis and embolism. Our case report highlights bilateral pulmonary embolism, one week after the second dose of the COVID-19 mRNA vaccine (Moderna) in a healthy newly married young women. Bangladesh J Medicine 2022; 33: 213-219